The risk of hepatocellular carcinoma in cirrhosis differs by etiology, age and sex: A Swedish nationwide population‐based cohort study. Issue 5 (1st May 2022) - Bengtsson, Bonnie; Widman, Linnea; Wahlin, Staffan; Stål, Per; Björkström, Niklas K.; Hagström, Hannes
Abstract: Background: Current risk estimates for hepatocellular carcinoma (HCC) in individuals with cirrhosis vary between studies. The risk has mostly been evaluated for single etiologies separately. Objectives: We examined the risk of HCC in Swedish outpatients with a new diagnosis of cirrhosis, aiming to identify subgroups with a particularly high risk for incident HCC. Methods: All patients with a first diagnosis of cirrhosis in the National Outpatient Register for whom the etiology of cirrhosis could be estimated were identified. Incident cases of HCC were ascertained until the end of 2016 using record linkage to national registers. The cumulative incidence of HCC across etiologies of cirrhosis, sex and age was calculated considering non‐HCC death as a competing risk. Results: We identified 15, 215 individuals with cirrhosis. The incidence rate for HCC in cirrhosis was 23/1000 person‐years (95%CI = 22–24). Stratified on gender, it was 29/1000 person‐years (95%CI = 27–31) in men versus 14/1000 person‐years (95%CI = 13–16) in women. The cumulative incidence of HCC in cirrhosis was 8.3% (95%CI = 7.8–8.8) at 5 years and 12.2% (95%CI = 11.6–13.0) at 10 years. At 10 years, the lowest cumulative incidence was seen in women with alcohol‐related liver disease (4.3%) and the highest in men with viral hepatitis (26.6%). These figures also varied by age. Conclusions: The risk of HCC differs extensively across subgroups of etiologies of cirrhosis, age and sex, suggesting that initiation of HCC surveillance could be individually tailored.